RELEVANSI HAK KEKAYAAN INTELEKTUAL DENGAN HAK ASASI MANUSIA GENERASI KEDUA - Dharmawan, Ni Ketut Supasti (Faculty of Law Jenderal Soedirman University, 2014)
It is likely not easy to categorize IPR as human right. Based on the human right test and positivism approach, can be categorized into three schemes. : First, IPR is not human rights but it is under purely the dimension of law.Â Second, some aspects of IPR have potential conflict with human rights. Third, IPR is human rights by emphasizing property rights and individual rights. The relevancy between IPR and the second generation of human rights can be considered based on Article 27.2 UDHR, Article 15 ICESCR and it General Comment No. 17 thatÂ emphases the recognition and protection of art and literary works. Key words: human right, IPR, relevancy, second generation